Determination of Reproduction Cost with Index Numbers - Troxel, C. Emery (Quarterly Journal of Economics, 1938)
I. Use of index numbers by Commissions, 105.— II. Advantages of the method, 107.— III. Suggested method of constructing such indexes, 108.— Legal requirements which must be met, 111.— Practical difficulties, 112.— Indexes must be supplemented, 114.— IV. Prospect of acceptance by the Courts, 115.